Rational cubic Bezier curve and it’s application in designing Jawi writing / Siti Asmah Mohamed, Rafizah Kechil and Shakirah Mohd Abd. Rahman. - Mohamed, Siti Asmah; Kechil, Rafizah; Mohd Abd. Rahman, Shakirah (2011)
Jawi writing is different from other characters such as Roman script, Latin. Jawi writing has a unique form, since it is more curvy compared to other script. The Jawi writing has different forms of writing skills, therefore, it needs excellent skills and attention. Conventionally the methodology in Jawi writing is designed by using the outline technique form. The first step of the whole process of Jawi writing’s outline generation is to get the digitized image of a character, detections of boundary, corner points and segmentation and lastly fitting the optimal curve segment. This paper will give a brief description of the Jawi writing generation by using equation of rational cubic Bezier curve for considered values of weight. Only changes in the weight are considered to generate the shape of Jawi writing. By finding the correct weights, the Jawi writing which are generated are smooth and get nearest to the digitized image.